Women's mental health and COVID-19: increased vulnerability and inequalities - Arilha, Margareth; Carvalho, Adriana P.; Forster, Thais A.; Rodrigues, Carla V. M.; Briguglio, Bianca; Serruya, Suzanne J. (Frontiers in Global Women's Health, 2024)
IntroductionThe impact of COVID-19 on mental health has become a relevant object of research. Studies have demonstrated that women have experienced greater mental health challenges, highlighting the importance of public health systems to address women's specific needs.MethodsThis literature review explores the effects of the coronavirus pandemic on psychological distress among women, aiming to provide a comprehensive understanding of the subject and to explore how these research findings can guide public mental health care responses in crisis settings. A total of 131 studies were analyzed and four dimensions were discussed: study characteristics, factors impacting women's mental health in the pandemic setting, particularities of pregnancy and the postpartum period, and proposed interventions. Most studies exclusively addressed populations of adult women, predominantly during pregnancy and the postpartum period.ResultsAnxiety, depression, and stress were the most common outcomes. Lower education and income, preexisting mental health problems, and living alone or with children were risk factors for higher levels of anxiety and depression.DiscussionA comprehensive care approach supported by public health policies and focused on intersectional factors, including race, socioeconomic status, and access to resources, is necessary to improve women's mental health care response in future crises.